Integrating PZT layer with tuned mass damper for simultaneous vibration suppression and energy harvesting considering exciter dynamics: An analytical and experimental study. (3rd March 2023) - Rezaei, Masoud; Talebitooti, Roohollah; Liao, Wei-Hsin; Friswell, Michael I
Highlights: Simultaneous Energy harvesting and vibration suppression by a TMD is investigated Electromechanical model is developed to capture shaker force drop off at resonances Constant voltage sweep is proposed to investigate the absorber performance The proposed coupled model of structure-shaker is validated by experiments Simulations and experiments reveal the advantages of exploiting the proposed model The TMD is efficient and applicable in reducing vibration and harvesting energy Abstract: This paper analytically and experimentally investigates the potential of a tuned mass damper (TMD) with an integrated piezoelectric layer for simultaneous energy harvesting and vibration suppression. The system investigated is composed of a main beam that is excited by a shaker. A TMD comprising a unimorph piezoelectric beam is attached to the main beam. The shaker force drops at the system resonance frequencies means that a constant force sine sweep is difficult in practice, and does not allow model validation and empirical assessment of the TMD. Also, the force drop off phenomenon and an accurate validated shaker model are vital for the modelling, analysis and validation of nonlinear dynamic systems. This paper validates and analyses a linear model, in preparation for future studies of a nonlinear vibration absorber and energy harvester. Therefore, the force drop off phenomenon is examined comprehensively, and a constant shaker input voltage sweep is proposed instead of a constant force sweep. The continuous electromechanical equations governing the coupled system of the main beam-TMD-shaker are developed. The proposed model is then utilized to examine the shaker force drop off, TMD efficiency, and shaker electrical characteristics. The results show that the constant voltage sweep works well to investigate the performance of the TMD and capture the shaker force drop off phenomenon. The TMD suppresses the host structure vibration and harvests energy efficiently, and is demonstrated by extensive experimental investigations. The model is validated by the experiments, including the force drop off. The system parameters have significant effects on the dynamical response of the coupled system and the energy harvested; the effects on the harvested power, reduced vibration, applied force, and force drop off frequencies are demonstrated. Overall, the TMD is shown to be efficient and applicable in reducing vibration and harvesting energy.